2019
DOI: 10.1021/acsnano.9b02209
|View full text |Cite
|
Sign up to set email alerts
|

Josephson Field-Effect Transistors Based on All-Metallic Al/Cu/Al Proximity Nanojunctions

Abstract: We demonstrate proximity-based all-metallic mesoscopic superconductor-normal metalsuperconductor (SNS) field-effect controlled Josephson transistors (SNS-FETs) and show their full characterization from the critical temperature T c down to 50 mK in the presence of both electric and magnetic field. The ability of a static electric field -applied by mean of a lateral gate electrode-to suppress the critical current I s in a proximity-induced superconductor is proven for both positive and negative gate voltage valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 42 publications
12
73
1
Order By: Relevance
“…As in similar experiments [1,2,6,7,[9][10][11], the critical current can be reduced, up to complete suppression at the critical gate voltage V C…”
Section: A Electric Field Vs In-and Out-of-plane Magnetic Fieldsupporting
confidence: 69%
See 1 more Smart Citation
“…As in similar experiments [1,2,6,7,[9][10][11], the critical current can be reduced, up to complete suppression at the critical gate voltage V C…”
Section: A Electric Field Vs In-and Out-of-plane Magnetic Fieldsupporting
confidence: 69%
“…Recently, it has been shown that the superconducting (SC) properties of metallic Bardeen-Cooper-Schrieffer (BCS) superconductors can be influenced via electrostatic gating [1]. The most striking effect: reduction and suppression of the critical supercurrent, has been broadly demonstrated in metallic nanowires [2][3][4] and Dayem bridges [5][6][7][8] made of titanium, titanium nitrate, aluminum, niobium, and vanadium, as well as in aluminum-copper-aluminum Josephson junctions [9]. Moreover, recent experiments have probed the effect of electrostatic gating on the SC phase in a SQUID [10], and on the nature of the switching current distributions in gated titanium Dayem bridges [11].…”
Section: Introductionmentioning
confidence: 99%
“…The quenching of the supercurrent is symmetric for V G −→ −V G for bath temperatures between 20 mK and 3 K, as shown in Figure 1c. As reported in conventional experiments [2][3][4]9], widening of the plateau in which the gate voltage is not effective is visible as the temperature rises. The suppression of the supercurrent can be observed up to a temperature of 3 K, with complete suppression at |V G | = 40 V for T > 2 K. Notably, the suppression of I S is visible up to a temperature of 3 K because the gating affects a localized region of the superconductor around the constriction [24].…”
Section: Niobium Gate-controlled Transistorsupporting
confidence: 59%
“…The dependence of I S [2][3][4][5][6]9,23,26,31] on the gate voltage is shown to acquire the I S vs. V G characteristics as a function of bath temperature. Figure 6b shows that the supercurrent vanishes for |V G | 34 V and that such a value appears to be independent from the bath temperature.…”
Section: Nonthermal Origin Of Supercurrent Suppression In Gated All-mmentioning
confidence: 99%
See 1 more Smart Citation